Decompression Alone in the Setting of Adult Degenerative Lumbar Scoliosis and Stenosis: A Systematic Review and Meta-Analysis. Issue 3 (April 2023) - Echt, Murray; De la Garza Ramos, Rafael; Geng, Eric; Isleem, Ula; Schwarz, Julia; Girdler, Steven; Platt, Andrew; Bakare, Adewale A; Fessler, Richard G; Cho, Samuel K
Study Design: Systematic review and meta-analysis. OBJECTIVESSurgical decompression alone for patients with neurogenic leg pain in the setting of degenerative lumbar scoliosis (DLS) and stenosis is commonly performed, however, there is no summary of evidence for outcomes. Methods: A systematic search of English language medical literature databases was performed for studies describing outcomes of decompression alone in DLS, defined as Cobb angle >10˚, and 2-year minimum follow-up. Three outcomes were examined: 1) Cobb angle progression, 2) reoperation rate, and 3) ODI and overall satisfaction. Data were pooled and weighted averages were calculated to summarize available evidence. Results: Across 15 studies included in the final analysis, 586 patients were examined. Average preoperative and postoperative Cobb angles were 17.6˚ (Range: 12.7 - 25˚) and 18.0 (range 14.1 - 25˚), respectively. Average change in Cobb angle was an increase of 1.8˚. Overall rate of reoperation ranged from 3 to 33% with an average of 9.7%. Average ODI before surgery, after surgery, and change in scores were 56.4%, 27.2%, and an improvement of 29% respectively. Average from 8 studies that reported patient satisfaction was 71.2%. Conclusions: Current literature on decompression alone in the setting of DLS is sparse and is not high quality, limited to patients with small magnitude of lumbar coronal Cobb angle, and heterogenous in the type of procedure performed. Based on available evidence, select patients with DLS who undergo decompression alone had minimal progression of Cobb angle, relatively low reoperation rate, and favorable patient-reported outcomes.